Development of Nutrient-Rich Injera Using Amaranthus Leaf/Grain and Teff Flours: A Study on Nutritional Value, Sensory Characteristics, and Storage Stability - Betelhem Abera; Ramesh Duraisamy; Tewodros Birhanu; Beyene Gurbo; Ketemaw Salelign (International Journal of Food Science)
Teff (Eragrostis tef, Zucc) is the smallest grain commonly cultivated in Ethiopia and Eritrea and is used mainly to prepare pancake-like staple food called flatbread (Injera). It has substantial national and global recognition due to its nutraceutical benefits and its gluten-free nature. Flatbread, a functional food for health promotion, can be enhanced with less mineral-rich crops like Amaranthus, which are often underutilized, to increase its nutritional and mineral content. Thus, the study is aimed at studying the nutritional, sensory, and storage period of flatbread by incorporating amaranth leaves and grain powders into teff flour. Experiments were designed (using Minitab software, v.19.1), and flatbread was prepared by altering the proportions (grams) of Amaranthus leaf and grain flour incorporated with teff flour in ratios of 2:98, 4:96, 6:94, 8:92, and 10:90 (w/w), teff being the significant component in each blend. The results revealed that most of the nutritive components (except carbohydrates and chromium (Cr)) improved significantly due to the incorporation of both (Amaranthus leaf and grains). Minerals such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), iron (Fe), and zinc (Zn) increased noticeably (in percent), ranging from 10% to 12.2%, 0.02%–0.41%, 3%–4.4%, 0.33%–2.2%, 5.7%–10%, and 4.9%–28.7%, respectively. Furthermore, lower proportions of Amaranthus grain flour (2, 4, and 6 g blending) and leaf flour (2–10 g blending) significantly extended the storage period of blended flatbread up to 6–7 days, where higher proportions of Amaranthus grain (8 and 10 g blending) are expected to preserve the flatbread Injera up to 9–10 days, surpassing the 3–4 days of the control (100 g teff flour). Therefore, novel teff–Amaranthus blended food can be produced by means of a cost-effective and easy-to-produce new integrated teff–Amaranthus blended food that can enhance the nutritional value and shelf life of the existing teff Injera.